Wishes, beliefs, and jealousy: use of mental state terms in Cinderella retells after traumatic brain injury - Greenslade, Kathryn J.; Honan, Cynthia; Harrington, Lauren; Kenealy, Laura; Ramage, Amy E.; Bogart, Elise (Frontiers in Human Neuroscience, 2024)
Traumatic brain injury (TBI) negatively impacts social communication in part due to social cognitive difficulties, which may include reduced mental state term (MST) use in some discourse genres. As social cognitive difficulties can negatively impact relationships, employment, and meaningful everyday activities, assessing and treating these difficulties post-TBI is crucial. To address knowledge gaps, the present study examined MST use in the narrative retells of adults with and without severe TBI to compare between-group performance, evaluate changes over the first two years post-TBI, and investigate the impact of participant and injury-related variables. The total number of MSTs, ratio of MSTs to total utterances, and diversity of MSTs were identified in the Cinderella narratives of 57 participants with no brain injury and 57 with TBI at 3, 6, 9, 12, and 24-months post-TBI. Reduced MST use in participants with TBI was found at 3, 6, 9, and 12-months post-TBI, but these reductions disappeared when story length (total utterances) was accounted for. Further, MST diversity did not differ between groups. Similarly, although the total number of MSTs increased over time post-TBI, no changes were observed in the ratio of MSTs to total utterances or MST diversity over time. Injury severity (post-traumatic amnesia duration), years of education, and verbal reasoning abilities were all related to MST use. Overall, although individuals used fewer MSTs in complex story retells across the first year following severe TBI, this reduction reflected impoverished story content, rather than the use of a lower ratio of MSTs. Further, key prognostic factors related to MST use included injury severity, educational attainment, and verbal reasoning ability. These findings have important implications for social communication assessment and treatment targeting social cognition post-TBI.